Perinatal Parenting Stress, Anxiety, and Depression Outcomes in First-Time Mothers and Fathers: A 3- to 6-Months Postpartum Follow-Up Study - Vismara, Laura; Rollè, Luca; Agostini, Francesca; Sechi, Cristina; Fenaroli, Valentina; Molgora, Sara; Neri, Erica; Prino, Laura E.; Odorisio, Flaminia; Trovato, Annamaria; Polizzi, Concetta; Brustia, Piera; et al. (Frontiers in Psychology, 2016)
Objective: Although the proven link between parenting stress, postnatal depression and anxiety, no study has investigated such relationship among fathers and mothers. The specific aims of this study were: 1) to investigate whether there were any differences between first-time fathers’ and mothers’ postnatal parenting stress, anxiety and depression symptoms and to see their evolution between 3 and 6 months after the child’s birth; 2) to explore how one’s own parenting stress and anxiety levels and the anxiety-depressive symptoms of the partner contribute to parental postnatal depression. Method: The sample was composed by 362 parents – 181 couples - (mothers’ MAge = 35.03, SD = 4.7; fathers’ MAge = 37.9, SD = 5.6) of a healthy baby. At three (T1) and six months (T2) postpartum, both parents filled out, in a counterbalanced order, the Parenting Stress Index-Short Form, the Edinburgh Postnatal Depression Scale and the State-Trait Anxiety Inventory. Results: Analyses showed that, compared to fathers, mothers reported higher scores on postpartum anxiety, depression and parenting stress. Scores on all measures for both mothers and fathers decreased from T1 to T2. However, path analyses suggested that the persistence of both maternal and paternal postnatal depression were influenced directly by one’s own levels of anxiety and parenting stress as well as by the presence of partner’s depression. Discussion: The study pointed out the relevant impact and effects of both maternal and paternal stress, anxiety and depression symptoms during the transition to parenthood. Therefore, in order to provide efficacious, targeted, early interventions, perinatal screening should always be directed to both parents.